Analysis of the effect of tofu industrial waste on dug well water quality - Sara Antoneta Atakari; Zakarias Mautuka; Martasiana Karbeka; Loth Botahala (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2020)
The industrial tofu factory located in Lautingara Kelurahan Kalabahi Tengah, where the remaining liquid waste is channeled directly into the reservoir without prior treatment, can affect water quality in the dug wells. The purpose of this study was to determine the quality and feasibility of dug well water as drinking water-based on parameters of pH, BOD, COD, nitrite, and nitrate of dug well water, which is suspected to be contaminated by the presence of tofu waste. The results showed that the pH value and nitrite value (NO2-) of the three dug well water samples in Lautingara met the drinking water quality standards, while the BOD, COD, and nitrate (NO3-) values in the three dug well water samples in Lautingara did not meet the values quality standards and not suitable for drinking water.